2019
DOI: 10.1148/radiol.2019182126
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration of the Substantia Nigra after Ipsilateral Infarct: MRI R2* Mapping and Relationship to Clinical Outcome

Abstract: O utcomes after stroke may include motor, cognitive, and/ or emotional impairment (1,2). Some of these longterm sequelae are the result of the brain tissue injured by infarction. However, long-term clinical outcome may also be impacted by delayed neurodegeneration of remote but functionally or anatomically connected areas that become disconnected as a result of primary ischemic injury (3). The substantia nigra (SN) is one brain region suspected to be affected after infarction, in view of its large array of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Our result was consistent with reported findings in previous studies [14,18,29,[54][55][56][57], where an increase in iron deposition level in basal ganglia and thalamus were confirmed poststroke. However, only Gattringer et al [58] did not observe a relationship between the damage severity and the increased iron deposition in DGM regions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our result was consistent with reported findings in previous studies [14,18,29,[54][55][56][57], where an increase in iron deposition level in basal ganglia and thalamus were confirmed poststroke. However, only Gattringer et al [58] did not observe a relationship between the damage severity and the increased iron deposition in DGM regions.…”
Section: Discussionsupporting
confidence: 94%
“…We observed partial improvements in the contralesional brain hemisphere, maybe due to an active reorganization [ 50 , 59 , 60 ]. There are also studies showing that motor performance is related to the amount of iron in the basal ganglia [ 56 ]. In our study, in all three patients, iron deposition level was decreased after rehabilitation accompanied with increasing the motor activation in fMRI, with a negative correlation.…”
Section: Discussionmentioning
confidence: 99%
“…As far as is currently known, CMBs are similar to lacunar infarcts and WMH in that they can affect the cortex by decreasing the amount and intensity of connections in the structure network (Liu et al, 2020 ). According to the remote effect of cerebral infarction, we want to propose a hypothesis (Linck et al, 2019 ). Local microhemorrhage induces red cell lysis and releases hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…When degeneration of nerve fibers occurs in any of the above parts or nerve conduction function is damaged by insufficient blood supply, iron cannot be excreted normally and excessive iron can deposit accordingly ( 41 ). Linck et al ( 42 ) utilized R2 * mapping to explore iron alterations of SN in patients with supratentorial ischemic stroke, and found that SN ipsilateral to the lesion presented greater iron content 1 year after stroke. Indeed, our results of both ACAS and PCAS patients could indirectly demonstrate the existence of known fibrous pathways between SN and basal ganglia.…”
Section: Discussionmentioning
confidence: 99%